2003
DOI: 10.1211/0022357021080
|View full text |Cite
|
Sign up to set email alerts
|

Personalised prescribing for asthma - is pharmacogenetics the answer?

Abstract: An individual's response to anti-asthma medication is likely to arise from a complex interaction between social, environmental and inherited factors. Studies indicate that genetic factors may account for 60-80% of the heterogeneity in treatment responsiveness in asthmatics. Identifying the genetic variants responsible may potentially lead to the development of novel treatments, improved effectiveness in the use of existing treatments and better prediction of efficacy in phase II and III trials. This article wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…Indeed, a thorough understanding of mechanisms may lead to not only isolation of genetic determinants, but also more effective pharmacologic treatment. 31 Although much needs to be learned about the pathophysiology of asthma, the major mechanism is reversible obstruction of the small airways, with airway inflammation being a predominant finding. 32,33 The inflammatory response of asthma involves numerous mediators, including eosinophils, mast cells, and CD 4ϩ lymphocytes.…”
Section: Asthmamentioning
confidence: 99%
“…Indeed, a thorough understanding of mechanisms may lead to not only isolation of genetic determinants, but also more effective pharmacologic treatment. 31 Although much needs to be learned about the pathophysiology of asthma, the major mechanism is reversible obstruction of the small airways, with airway inflammation being a predominant finding. 32,33 The inflammatory response of asthma involves numerous mediators, including eosinophils, mast cells, and CD 4ϩ lymphocytes.…”
Section: Asthmamentioning
confidence: 99%
“…[7][8][9][10][11] Moreover, the ␤ 2 AR has received extensive attention as a candidate gene (ADRB) for asthma. [12][13][14] The endogenous circulating ␤-agonist epinephrine has been reported to influence T-cell responses in heart failure patients, who typically have elevated levels of serum epinephrine. Yndestad et al reported that peripheral T cells, but not monocytes, from heart failure patients exhibit increased expression of chemokines, IFN-␥, interleukin-18 (IL-18), and tumor necrosis factor (TNF) superfamily genes.…”
Section: Introductionmentioning
confidence: 99%
“…This forecast on response generally reflects our limited knowledge on the physiopathology of asthma. Moreover, some components of these changes are possible to explain by many pharmacogenetics factors ( 17 ).…”
Section: Discussionmentioning
confidence: 99%